JALAN MENUJU HARMONI: MENGEMBANGKAN JIWA BERKARAKTER MELALUI IMPLEMENTASI TRI HITA KARANA (THK) DI SEKOLAH DASAR BERBASIS KEARIFAN LOKAL - Antara, I Kadek Arya; Setiawati, Ni Kadek; Dwijayanti AK, Kadek Prima; Agung, Anak Agung Gede (Pascasarjana Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the role and synergy of Tri Hita Karana (THK) values ​​in character formation of elementary school students based on local wisdom in Tabanan Regency, Bali. The study used a qualitative descriptive-analytical approach, with data collection techniques including observation, interviews, and documentation. The results indicate that Parahyangan values ​​play a role in building the foundation of students' religious character and discipline through the habituation of spiritual activities integrated into school routines. Pawongan values ​​strengthen students' social character through harmonious interaction patterns that foster empathy, cooperation, and a sense of social responsibility. Meanwhile, Palemahan values ​​shape ecological character through students' direct involvement in environmental conservation practices. The main findings of this study indicate that the synergy of Parahyangan, Pawongan, and Palemahan forms a holistic character education structure, where the spiritual, social, and ecological dimensions are mutually reinforcing and inseparable. Theoretically, this article expands the study of character education by offering Tri Hita Karana as an integrative conceptual framework based on local wisdom, capable of bridging moral-spiritual, social, and environmental approaches within a single, contextual and sustainable character education model in elementary schools.